The Impact of the Boko Haram Insurgency in Nigeria: A Multi Sectoral Analy - Dingji Maza Kangdim; Cemal Yorgancıoğlu; Kwopnan Ibrahim Bulus; Adamu Yakubu Muazu; Semshak Kassem Danladi (Siyasal: Journal of Political Sciences)
Using the Regional Security Complex Theory (RSCT) and qualitative methodological approach, this article examines the impact of the Boko Haram insurgency on the various sectors and arenas of security as proposed by proponents of the Copenhagen School of Security Studies. Findings of the article suggest that the presence and activities of this terror group have impacted the various arenas of security and have also created dire sub-regional and regional implications in spite of the various counter-measures designed by sub-regional and regional actors to counter the threat posed by the terror group. Therefore, to address this challenge, the article offers practical recommendations to critical and relevant actors involved in countering the presence of this group at the various political, military, societal, economic, environmental, sub-regional, and regional levels.